2003
DOI: 10.1080/13693780310001597368
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of <emph type="2">Paracoccidioides brasiliensis</emph> infection in armadillos (<emph type="2">Dasypus novemcinctus):</emph> an ecological study

Abstract: The fungus Paracoccidioides brasiliensis has been isolated from nine-banded armadillos (Dasypus novemcinctus) in different regions where paracoccidiodomycosis (PCM) is endemic. The link between PCM and these animals has provided the first valuable clue in the effort to elucidate the ecological niche of P. brasiliensis. The present study was aimed at correlating P. brasiliensis infection in armadillos with local ecological features and, if possible, the presence of the fungus in the soil in the Botucatu hyperen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 12 publications
3
57
0
6
Order By: Relevance
“…In this experimental study, we have also observed that P. brasiliensis is unable to grow in some soils containing high amounts of Exchangeable Aluminum (H+Al) and low Bases Saturation. These results also corroborate some previous reporting on P. brasiliensis isolation from armadillos in our endemic area, in which we aimed to address the associated ecological factors [55]. Firstly, positive-culture armadillos were observed living in both in clay and sandy soil; secondly, the frequency of animal infection was heterogeneous in the different counties composing our endemic area; and finally, all armadillos captured in a restricted site (from Pardinho County), where soil analysis had revealed a high concentration of Exchangeable Aluminum, proved to be negative for P. brasiliensis culture.…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencesupporting
confidence: 92%
See 2 more Smart Citations
“…In this experimental study, we have also observed that P. brasiliensis is unable to grow in some soils containing high amounts of Exchangeable Aluminum (H+Al) and low Bases Saturation. These results also corroborate some previous reporting on P. brasiliensis isolation from armadillos in our endemic area, in which we aimed to address the associated ecological factors [55]. Firstly, positive-culture armadillos were observed living in both in clay and sandy soil; secondly, the frequency of animal infection was heterogeneous in the different counties composing our endemic area; and finally, all armadillos captured in a restricted site (from Pardinho County), where soil analysis had revealed a high concentration of Exchangeable Aluminum, proved to be negative for P. brasiliensis culture.…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencesupporting
confidence: 92%
“…The demonstration of a high incidence of P. brasiliensis infection in the nine-banded armadillo, Dasypus novemcinctus, a wild mammal that typically has evolved in South America and lives immersed in soil [52][53][54][55][56][57][58], has opened new perspectives for comprehending the pathogen's ecology and evolution. In this animal species and also in the naked-tailed armadillo, Cabassous centralis [59], P. brasiliensis can be isolated regularly.…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis postulated that fish and aquatic birds would be required around the microniche to allow survival and dispersion of the fungus in nature (Conti-Díaz, 2007). Of ecological importance is the regular isolation of the fungus from armadillos (Dassypus novemcinctus, Cabassous centralis) captured in the endemic areas, some of which revealed internal lesions (Bagaggli et al, 2003). Dogs and other domesticated and feral animals have also been implicated (Ricci et al, 2004;Richini-Pereira et al, 2008).…”
Section: General Concepts On Ecologymentioning
confidence: 99%
“…Paracoccidioides has been repeatedly recovered from human clinical samples and tissues from some armadillo species (Dasypus novemcinctus) [11,12], and the first association with these animals was observed in the Amazon region by Naiff et al [13]. Although the Paracoccidioides was recovered from soil and related material in many situations, the exact places where this fungus exists in nature have not yet been determined; however, the soil continues to be an important element in the ecological study of this fungus [14].…”
Section: Epidemiologymentioning
confidence: 99%